Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1097/ncc.0000000000000636
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Smoking Cessation Counseling Scale Chinese Version in Taiwan

Abstract: Background Providing tobacco control (TC) and smoking cessation (SC) counseling is an important part of healthcare. An assessment tool to understand healthcare providers' experiences in providing SC counseling may enhance TC. Objective The aims of this study were to (1) translate and develop the Smoking Cessation Counseling Scale–Chinese version (SCCS-C) and (2) evaluate its psychometric properties in Taiwan. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
3
0
2
Order By: Relevance
“…Both the studies on the original version of the SCC and the validation study of the instrument in China assessed the structural validation of the SCC by means of exploratory factor analysis, but both reported the need to carry out confirmatory factor analysis studies in order to obtain more psychometric evidence (14,16,27) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the studies on the original version of the SCC and the validation study of the instrument in China assessed the structural validation of the SCC by means of exploratory factor analysis, but both reported the need to carry out confirmatory factor analysis studies in order to obtain more psychometric evidence (14,16,27) .…”
Section: Discussionmentioning
confidence: 99%
“…and adapted in China, showing construct validity and an internal consistency ranging from 0.56 to 0.79 for the instrument's 24 items (16) .…”
Section: Smoking Cessation Counseling Was First Validatedmentioning
confidence: 99%
“…En la evaluación psicométrica de la versión china del instrumento, este valor varió de 0,56 a 0,79 al analizar la estructura del instrumento con cuatro factores, valores muy cercanos a los alcanzados en este estudio, pero cuando el estudio chino analizó el instrumento con una estructura de tres factores, se obtuvo un coeficiente de alfa de Cronbach de 0,96 para el puntaje global y 0,94 para el dominio de asesoramiento avanzado, 0,93 para el dominio de asesoramiento básico y 0,80 para el dominio de derivación a servicios en comparación con la escala original (16) .…”
Section: Discussionunclassified
“…La Smoking Cessation Counseling fue validada y adaptada inicialmente en China, presentando validez de constructo y una consistencia interna que varía de 0,56 a 0,79 para los 24 ítems del instrumento (16) .…”
Section: Introductionunclassified
“…Although the 2014 Surgeon General's statement on the health successive of Smoking (50 Years) of Progress demonstrated that the spread of stream smoking is on the refuse, the report confirms the need further to monitor types of use for all tobacco products, particularly as the disparity in use persevere. Alternative forms of smoking use are rising in publicity among young 25 . Mousawi,2014, found that Iraqi studies on secondary school and university students reported smoking use rates spreading from (3.2-to 21%).…”
Section: Introductionmentioning
confidence: 99%